2004
DOI: 10.1111/j.1748-5967.2004.tb00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Silk Production after Mechanical Pulling Stimulation in the Ampullate Silk Glands of the Barn Spider, Araneus cavaticus

Abstract: Synthesis of protein by the major ampullate silk glands in the barn spider, Araneus cavaticus was stimulated by depleting the storage of silk protein in the ampulla by mechanically pulling fiber from the spigot. After this treatment, fine structural changes of the glandular epithelium during silk production were examined using light and transmission electron microscopes. In the process of rapid production, major secretory silk was synthesized at the tail region via rER of glandular epithelial cells, and was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 21 publications
0
20
0
3
Order By: Relevance
“…Previous studies have found that divergence of spider species correlates with evolution of the ampullate gland (Foelix 1996), and it has also been shown that selection and molecular events resulted in the evolution of the ampullate silk proteins (Craig & Riekel 2002). Like other araneid spiders, such as wandering spiders (Moon 1998; Moon & An 2005) and other web‐building spiders (Tillinghast & Townley 1986; Peters & Kovoor 1991; Moon 2002; Park & Moon 2002; Moon & Tillinghast 2004; Moon & An 2006), the ampullate glands were the largest silk glands observed in O. striatipes and were used for making draglines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that divergence of spider species correlates with evolution of the ampullate gland (Foelix 1996), and it has also been shown that selection and molecular events resulted in the evolution of the ampullate silk proteins (Craig & Riekel 2002). Like other araneid spiders, such as wandering spiders (Moon 1998; Moon & An 2005) and other web‐building spiders (Tillinghast & Townley 1986; Peters & Kovoor 1991; Moon 2002; Park & Moon 2002; Moon & Tillinghast 2004; Moon & An 2006), the ampullate glands were the largest silk glands observed in O. striatipes and were used for making draglines.…”
Section: Discussionmentioning
confidence: 99%
“…병상선은 종에 따라 수와 형태가 매우 다양한 것으로 알려져 있는데, 왕거미과의 거미들은 견사선과 토사관의 형태적 특성을 기 준으로 대병상선과 소병상선으로 구분되며 각각 전방적돌 기와 중방적돌기를 통해 연결되어 있다 (Moon & Tillinghast, 2004;Moon, 2012). 거미 실크의 물리적 특성을 비교한 결과에 의하면, 대병 상선에서 생성되는 dragline 실크의 강도(strength)는 4×10 9…”
Section: 고 찰unclassified
“…반면, 소병상선의 강 도는 대병상선의 1/4 정도이지만 신축율이나 파쇄 에너지는 케블라 섬유와 거의 동일한 것으로 보고되고 있다 (Gosline et al, 1984;Stauffer et al, 1994;Kaplan, 1998). 왕거미과의 거미에서 대병상선과 소병상선, 그리고 편상 선 등, 세 종류의 견사선이 특히 긴 분비관을 가지고 있는 본질적인 이유에 대해서는 강하고 질긴 섬유를 생성하기 위 한 구조라는 점에 의견의 일치를 보고 있는데 (Bell & Peakall, 1969;Peakall, 1969;Tillinghast & Townley, 1986, 1987, 추 락하는 자신의 체중을 지탱하거나, 포획되는 먹이의 가속도 를 효과적으로 완충시킬 수 있는 강하고 탄력성 있는 실크 가 이들 견사선으로부터 생성된다는 생태적 관찰 (Moon & Tillinghast, 2004)과 각 실크의 물리적 특성 (Stauffer et al, 1994;Kaplan, 1998 (Work, 1984;Knight & Vollrath, 1999. 생화학적 분석에 의하면, 분비낭의 내부에 액체상태로 간 직된 실크 단백질은 전형적인 α 나선(α helix) 구조로 이루 어져 있으나, 분비관을 통과하여 고체상의 섬유로 변형된 상태에서는 β 병풍(beta plated sheet) 구조를 가지게 되며 (Bell & Peakall, 1969;Andersen, 1970), 이러한 변형은 액체 상태의 실크 단백질이 가늘고 긴 분비관을 통과하는 과정 에서 수분이 소실됨으로써 이루어지는 것으로 추정되고 있 다 (Til-linghast et al, 1984;.…”
Section: 고 찰unclassified
See 1 more Smart Citation
“…). Although both types of silk can be produced in a sophisticated process through a sequential pathway from silk gland to spigot, most of our knowledge of the spider silk producing system focuses on the water‐insoluble fibrous silk, particularly the dragline silk spun by the major ampullate spigot on anterior spinneret (Vollrath & Knight ; Moon & Tillinghast ).…”
Section: Introductionmentioning
confidence: 99%